Entry, exit and productivity: empirical results for German manufacturing industries - Joachim Wagner (Institute for the Study of Labor (IZA), 2007)
Using panel data from Spain Farinas and Ruano (IJIO 2005) test three hypotheses from a model by Hopenhayn (Econometrica 1992): (H1) Firms that exit in year t were in t-1 less productive than firms that continue to produce in t. (H2) Firms that enter in year t are less productive than incumbent firms in year t. (H3) Surviving firms from an entry cohort were more productive than non-surviving firms from this cohort in the start year. Results for Spain support all three hypotheses. This paper replicates the study using unique newly available panel data sets for all manufacturing plants from Germany (1995-2002). Again, all three hypotheses are supported empirically.
urn:nbn:de:101:1-2008041580
Keywords: 330; Verarbeitendes Gewerbe; Produktivität; Unternehmensentwicklung; Markteintritt; Marktaustritt; Deutschland